Flea Diversity as an Element for Persistence of Plague Bacteria in an East African Plague Focus - Eisen, Rebecca J.; Borchert, Jeff N.; Mpanga, Joseph T.; Atiku, Linda A.; MacMillan, Katherine; Boegler, Karen A.; Montenieri, John A.; Monaghan, Andrew; Gage, Kenneth L. (PLoS ONE, 2012)
Plague is a flea-borne rodent-associated zoonotic disease that is caused by Yersinia pestis and characterized by long quiescent periods punctuated by rapidly spreading epidemics and epizootics. How plague bacteria persist during interepizootic periods is poorly understood, yet is important for predicting when and where epizootics are likely to occur and for designing interventions aimed at local elimination of the pathogen. Existing hypotheses of how Y. pestis is maintained within plague foci typically center on host abundance or diversity, but little attention has been paid to the importance of flea diversity in enzootic maintenance. Our study compares host and flea abundance and diversity along an elevation gradient that spans from low elevation sites outside of a plague focus in the West Nile region of Uganda (,725–1160 m) to higher elevation sites within the focus (,1380–1630 m). Based on a year of sampling, we showed that host abundance and diversity, as well as total flea abundance on hosts was similar between sites inside compared with outside the plague focus. By contrast, flea diversity was significantly higher inside the focus than outside. Our study highlights the importance of considering flea diversity in models of Y. pestis persistence.
Keywords: Flea Diversity; Plague Bacteria; East African Plague Focus